Synergistic control of Aphis fabae Scop. (Hemiptera: Aphididae) on faba bean using botanical extracts and predatory ladybirds - El Aalaoui, Mohamed; Kamal, Fatima Zahra; Rammali, Said; Ciobica, Alin; Albert, Cristina; Burlui, Vasile; Sbaghi, Mohamed (Frontiers in Sustainable Food Systems, 2025)
IntroductionAphis fabae Scop. (Hemiptera: Aphididae) poses a major threat to Vicia faba L. crops, demanding sustainable control strategies.MethodsWe assessed the single and combined efficacy of two predatory ladybirds—Coccinella septempunctata (CS) and Hippodamia convergens (HC)—with two 10% botanical extracts—Nicotiana glauca (NG) and Ricinus communis (RC) (Solanaceae)—against A. fabae under screenhouse conditions (25 ± 1°C; 60 ± 10% RH). Ten treatments, including imidacloprid (ICP, 20 mL hL−1) as a positive control, were tested in a randomized complete-block design (3 replicates × 7 plants). Ladybirds were released one-week post-treatment.Results and discussionCombined treatments were most effective in reducing A. fabae populations. By week 5, egg densities dropped from ~95 to 2.0 (RC + CS treatment) and 3.9 (RC + HC treatment), compared to 15.0 with imidacloprid (ICP). Motile stages declined to 10 (RC + CS treatment) and 15 (RC + HC treatment), versus 45 with ICP treatment. NG-based combinations showed moderate efficacy, while single treatments were less consistent. Ladybird establishment was not affected by extracts. C. septempunctata reached 10.2 motile stages per three leaves per plant in RC + CS treatment by week 5, compared to 8.7 in CS treatment. H. convergens reached 10.0 motile stages per three leaves per plant in RC + HC treatment. Plant visual scores peaked at 9.67 (RC + CS treatment) and 9.35 (RC + HC treatment), outperforming imidacloprid (visual score: 8.25). The synergy between R. communis or N. glauca extracts and ladybird predators offers an effective alternative to imidacloprid for A. fabae control. Field trials and timing optimization are recommended to integrate these tactics into faba-bean IPM programs.